Estudo comparativo sobre famílias de pré-escolares com deficiências, dificuldades escolares e desenvolvimento típico - Marins, Danielli Gualda (2018)
This study aimed to: (a) explore the possible risk and protection factors of families of children with disabilities, indicative of school difficulties and typical development, and (b) examine the relationships between parental variables. The participation of 15 Childhood Education teachers aimed to divide the children according to an assessment conducted by the Capacities and Difficulties Questionnaire (CDQ) and the academic part of the Social Skills Rating System (SSRS). In fact, 87 family members (mother, father or guardian) participated in the study, of which 27 had children with disabilities, 30 had children with signs of school difficulties and 30 had children with typical development. Data collection took place in seven municipal pre-schools. In order to meet the objectives, the family members answered, in the form of an interview, to six instruments: Brazil Criteria Questionnaire, Semistructured interview script, Shared and Engagement Routine Checklist between Family-School – parents’ version, Family Environment Resource Inventory (FERI), Family Needs Questionnaire (FNQ) and Social Support Questionnaire (SSQ). The qualitative data were analyzed through the elaboration of subcategories, with the participation of three experts. Quantitative data were analyzed using descriptive methods - measures of central tendency and dispersion. To compare the quantitative data between the three groups, the ANOVA test was used, as well as the chi-square test to perform the qualitative comparison between the groups. The results showed statistically significant differences between the groups. The parents/guardians of the group with children with typical development (GTD) presented better organization and routine supervision, as well as better relations with the school, specifically in relation to the parent-teacher and parent-student dyads. The sociodemographic aspects of the parents/guardians of the group with children with low academic performance and behavioral problem (GAP/BP), together with the paid activity practiced outside the home by most of the participants, have possibly impacted on the difficulty they had to meet at home, follow up on their children’s homework, and engage directly with the school institution. In the case of the group of children with disabilities (GD), even though it was ascertained that the children in this group did not often perform activities at home, established routines for daily life activities and took walks, it was found that they established better relationships with the school than the group of GAP/BP. The discussions and hypotheses raised suggested that the school institutions which GD, GAP/BP and GTD children attended to were related differently to each of their families, assuming that the best interactions were with those with children with typical development. In view of the findings, this research confirmed the initial questions that there were particularities among the families of the three groups, considering that children with typical development had protective aspects from their immediate context to the relations that indirectly affected their academic and behavioral performance. The families whose children showed signs of school difficulties were the group that showed the most unfavorable conditions at all environmental levels ascertained, as well as the identification of a relationship with the most precarious school, either because of their own cultural and socioeconomic conditions or by the posture of the institution. In families where the children had a disability, it was observed the presence of risk and protection mechanisms acting simultaneously, since several conditions were favorable to their development, but the lack of practical and instrumental support may have led to some types of demands.